Autoimmune complications associated with hepatitis A virus infection in children - ERTEM ŞAHİNOĞLU, DENİZ (LIPPINCOTT WILLIAMS & WILKINS, 2001)
Hepatitis A virus infection is usually a self-limited disease during childhood. Autoimmune manifestations are rarely reported among patients. We describe two children with acute hepatitis A infection who developed immune thrombocytopenia and hepatic venous thrombosis during the course of acute infection. Antiphospholipid antibodies were increased in both of them during the thrombocytopenic and thrombotic complications and decreased during the resolution of these events.
Keywords: hepatitis A; antiphospholipid antibody; thrombocytopenia; thrombosis; BUDD-CHIARI SYNDROME; LUPUS ANTICOAGULANT; ANTIBODIES; PURPURA